Peningkatan Ketrampilan Smash Permainan Bola Voli Melalui Metode Resiprokal - Siswanto, Heri (Universitas Negeri Semarang, 2012)
The purpose of this study to determine whether the application through reciprocal method can improve the skills of Grade 3 Agronomy 5 smash SMK Negeri 1 Waterford in the second semester of the school year 2011/2012.Dalam tests used in data collection techniques to determine student learning outcomes and non-test techniques such as observation sheets through observations to determine the learning process. The research method used was Classroom Action Research to perform two actions in two cycles. From the results of this research note an improvement in learning outcomes and learning processes. From the initial conditions to an increase in cycle 1 average value of 71.20 to 75.02, an increase of 4.22 percent. In the two-cycle is the last cycle the average value is 85.26, which means an increase of 10.24 per cent of the initial conditions. Similarly, the learning process showed an increase in activity and creativity of students and teachers. It can be concluded that through the implementation of the reciprocal method can improve the skills of the game of volleyball smash Grade 3 Agronomy 5 SMK Negeri 1 Waterford in the second semester of academic year 2011/2012.